A revolta das canetas de 2016: um estudo de caso das ocupações secundaristas em Fortaleza – a Escola Adauto Bezerra - Oliveira, Danielle Rodrigues de (2022)
The research investigated the experiences of high school students from Escola de Ensino Médio Governador Adauto Bezerra in occupations in 2016, understanding how participation in this process contributed to the political and intellectual formation of students. We reflect on the motivations that led students to join the movement of occupations in public schools, how students changed school environments, what was the relationship between the school community and the occupation, what were the strategies and tactics of the high school students during the movement. . We also investigated the implications of returning to school after the occupations ended and how the experiences produced and left by the occupation had an impact on the students' education. The research used as theoretical reference the thoughts of Certeau (2014), Foucault (2014) and Bauman (2013). Regarding the methodology, initially, questionnaires were applied to the students, and important information about the occupations was collected. Subsequently, we contacted the squatters of the Adauto Bezerra School who stood out in any of the commissions (food, security, press, information, cleaning and external relations) to carry out the interviews. In this case study, we concluded that participation in the occupation contributed to the formation of students both in the cognitive field and in political awareness. Most of our interviewees managed to enter higher education and highlighted that the engagement in the occupation made them currently have a youth role in the University.